Subgroup analysis of Japanese patients in a phase 3 study of lenvatinib in radioiodine‐refractory differentiated thyroid cancer. Issue 12 (2nd November 2015) - Kiyota, Naomi; Schlumberger, Martin; Muro, Kei; Ando, Yuichi; Takahashi, Shunji; Kawai, Yasukazu; Wirth, Lori; Robinson, Bruce; Sherman, Steven; Suzuki, Takuya; Fujino, Katsuki; Gupta, Anubha; et al.
Abstract : Lenvatinib significantly prolonged progression‐free survival (PFS) versus placebo in patients with radioiodine‐refractory differentiated thyroid cancer (RR‐DTC) in the phase 3 Study of (E7080) Lenvatinib in Differentiated Cancer of the Thyroid (SELECT) trial. This subanalysis evaluated the efficacy and safety of lenvatinib in Japanese patients who participated in SELECT. Outcomes for Japanese patients (lenvatinib, n = 30; placebo, n = 10) were assessed in relationship to the SELECT population (lenvatinib, n = 261; placebo, n = 131). The primary endpoint was PFS; secondary endpoints included overall survival, overall response rate, and safety. Lenvatinib PFS benefit was shown in Japanese patients (median PFS: lenvatinib, 16.5 months; placebo, 3.7 months), although significance was not reached, presumably due to sample size (hazard ratio, 0.39; 95% confidence interval, 0.10–1.57; P = 0.067). Overall response rates were 63.3% and 0% for lenvatinib and placebo, respectively. No significant difference was found in overall survival. The lenvatinib safety profile was similar between the Japanese and overall SELECT population, except for higher incidences of hypertension (any grade: Japanese, 87%; overall, 68%; grade ≥3: Japanese, 80%; overall, 42%), palmar–plantar erythrodysesthesia syndrome (any grade: Japanese, 70%; overall, 32%; grade ≥3: Japanese, 3%; overall, 3%), and proteinuria (any grade: Japanese, 63%; overall, 31%; grade ≥3: Japanese, 20%; overall, 10%). Japanese patients had more dose reductions (Japanese, 90%; overall, 67.8%), but fewer discontinuations due to adverse events (Japanese, 3.3%; overall, 14.2%). There was no difference in lenvatinib exposure between the Japanese and overall SELECT populations after adjusting for body weight. In Japanese patients with radioiodine‐refractory differentiated thyroid cancer, lenvatinib showed similar clinical outcomes to the overall SELECT population. Some differences in adverse event frequencies and dose modifications were observed. Clinical trial registration no.: NCT01321554. Abstract : Lenvatinib significantly prolonged progression‐free survival (PFS) vs placebo in patients with radioiodine‐refractory differentiated thyroid cancer (RR‐DTC) in the phase 3 SELECT trial. This subanalysis evaluated the efficacy and safety of lenvatinib in Japanese patients from SELECT. In Japanese patients with RR‐DTC, lenvatinib demonstrated similar clinical outcomes as the overall SELECT population. Some differences in adverse event frequencies and dose modifications were observed.